1998
DOI: 10.1046/j.1365-8711.1998.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

The z=2.72 galaxy cB58: a gravitational fold arc lensed by the cluster MS 1512+36

Abstract: Using HST WFPC2 V-and R-band data of the z = 0.37 cluster MS1512+36 we show that the z = 2.72 'protogalaxy' cB58 is not extraordinarily luminous intrinsically but lensed into a gravitational fold arc by the cluster. The arc has a surface brightness weighted axis ratio of 1 : 7, is marginally resolved in width and about 3 ′′ long. Its counterimage was identified and found to be very compact (r 1/2 = 2.4 − 4.0h −1 50 kpc in a q 0 = 0.05 cosmology). In addition, we found three further multiple image systems, one … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 27 publications
8
91
0
Order By: Relevance
“…Conditions were mostly photometric during both Keck runs, and the typical seeing in the K band was FWHM. 0A .5È0A .6 Ellingson et al 1996) have been corrected for the gravitational magniÐcation by a factor of 30 derived by Seitz et al 1998. h NIRSPEC N4 band spans the wavelength range 1.3È1.6 km.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Conditions were mostly photometric during both Keck runs, and the typical seeing in the K band was FWHM. 0A .5È0A .6 Ellingson et al 1996) have been corrected for the gravitational magniÐcation by a factor of 30 derived by Seitz et al 1998. h NIRSPEC N4 band spans the wavelength range 1.3È1.6 km.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Owing to its gravitationally lensed nature, MS 1512-cB58 is one of the brightest known LBGs. This object is at z ∼ 2.73 and has a luminous mass of ∼10 10 M , a star formation rate ψ(t sf ) ∼ 40 M yr −1 (Pettini et al 2002) and an effective radius of r L ∼ 2 kpc (Seitz et al 1998), for a Ω m = 0.3, Ω Λ = 0.7, h = 0.70 cosmology. Pettini et al (2002) concluded that the abundances of O, Mg and Si are ∼2/5 of their solar values, whereas [Fe/H] = -1.15, hence underabundant by a further factor of >3 with respect to the other elements.…”
Section: Lyman Break Galaxiesmentioning
confidence: 99%
“…Assuming for an Im-type SED ( Seitz et al 1998, who give R \ 23.9 and after demagniÐcation. Applying a distance K AB \ 23.0 modulus of 46.8 mag, a K-correction bandpass term of 1.4 mag, and assuming B[V \ 0.27 for an Im-type spectral energy distribution (Fukugita et al 1995) yields the Ðnal rest-frame B magnitude of [22.1.…”
Section: Evolution Of Chemical Propertiesmentioning
confidence: 99%